Confidence and Information in Strategy-Proof School Choice - Müge Süer; Michel Tolksdorf; Vincent Meisner; Sokol Tominaj (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2025)
Contrary to classical theory, we provide experimental evidence that preference reports in a strategy-proof school-choice mechanism systematically depend on beliefs. We employ a "hard-easy gap" to exogenously vary students' beliefs about their priority rank. As predicted, underconfidence induces more manipulation and thus more justified envy than overconfidence. The effect of priority information on justified envy crucially depends on the initial beliefs and the real priority ranks: while top students always gain, non-top students lose from this information. In total, correcting overconfidence/underconfidence increases/decreases justified envy. Finally, we confirm that additionally providing information on school availability through a dynamic implementation of the mechanism reduces justified envy compared to priority information alone.
Keywords: C92; D47; 330; Market design; school choice; overconfidence; strategy-proofness; information